2016
DOI: 10.1186/s13054-016-1276-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a causal link between sepsis and long-term mortality: a systematic review of epidemiologic studies

Abstract: BackgroundIn addition to acute hospital mortality, sepsis is associated with higher risk of death following hospital discharge. We assessed the strength of epidemiological evidence supporting a causal link between sepsis and mortality after hospital discharge by systematically evaluating the available literature for strength of association, bias, and techniques to address confounding.MethodsWe searched Medline and Embase using the following ‘mp’ terms, MESH headings and combinations thereof - sepsis, septic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 87 publications
5
87
2
4
Order By: Relevance
“…We found that patients who survived after sepsis had a 2.2-fold increased risk of mortality compared with elderly AKI patients who underwent CRRT without sepsis. This finding was consistent with previous studies that reported an increased risk of mortality after sepsis or ICU admission in an elderly or general population [2831]. It is uncertain whether the increased risk of post-sepsis mortality in our patients was a simple reflection of the trajectory of pre-morbid condition or sepsis itself.…”
Section: Discussionsupporting
confidence: 93%
“…We found that patients who survived after sepsis had a 2.2-fold increased risk of mortality compared with elderly AKI patients who underwent CRRT without sepsis. This finding was consistent with previous studies that reported an increased risk of mortality after sepsis or ICU admission in an elderly or general population [2831]. It is uncertain whether the increased risk of post-sepsis mortality in our patients was a simple reflection of the trajectory of pre-morbid condition or sepsis itself.…”
Section: Discussionsupporting
confidence: 93%
“…Select older data coming from high income countries suggest that sepsis survivors have worse longterm outcomes [138,139]. A recent systematic review of 43 studies, among which only 16 had control arms to allow assessment of attributable mortality, failed to clearly demonstrate a causal relationship between sepsis and post-acute mortality [140]. This systematic review raised the alternative hypothesis that the increased mortality after sepsis was probably related to the pre-existing disease comorbidity.…”
Section: Post-icumentioning
confidence: 94%
“…In 16 studies reported in a systematic review with non-sepsis controls, the main predictor variables for post-acute mortality were age, male sex, tobacco use, health-care associated pneumonia, use of immunosuppressant drugs, HIV infection, cancer, previous cardiovascular or cerebrovascular disease and the degree of organ dysfunction [140]. However, even in well-controlled studies, it is difficult to identify among these factors those related to the sepsis-attributable mortality.…”
Section: What Are the Predictors Of Sepsis Long-term Morbidity And Momentioning
confidence: 99%
“…Because of the limitations of existing literature, experts have recently called for additional epidemiological studies of late mortality attributable to sepsis that use patient level data to deal with confounding. 12 To guide the development of future treatments, we measured the excess late (31 days to two years) mortality directly attributable to sepsis-and not to the comorbidities and sociodemographic factors that predispose one to developing sepsis. We looked at patients with sepsis compared with three control groups: adults not currently in hospital, patients in hospital with non-sepsis infection, and patients in hospital with an acute sterile inflammatory process.…”
Section: Introductionmentioning
confidence: 99%